Modern methods of energy saving in industrial enterprises - Iles I. Bakhadirov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: the industrial sectors of Uzbekistan — metallurgy, petrochemical, construction, machinery and textiles - are the largest consumers of electricity, and the growth of their production analyze the load on the energy system and increases the cost of production. Government programs and updated laws on energy conservation require a reduction in specific energy consumption and the introduction of energy-efficient technologies. Energy saving today is not only about reducing costs, but also meeting international environmental requirements, In addition, in Uzbekistan and a number of other countries, the introduction of modern energy saving methods is supported by government programs, standards and tax benefits. Therefore, the study of modern methods of saving electricity is an urgent task for enterprises, researchers and future specialists, ensuring sustainable development and reducing operating costs. Aim: to analyze modern methods of saving electricity at industrial enterprises of the Republic of Uzbekistan and to study in detail the efficiency of variable frequency electric drives (VFD) as one of the key energy saving tools. Methods: The study utilized systemic, comparative, and analytical approaches to comprehensively evaluate modern energy-saving technologies at industrial enterprises. Thus, the combination of applied methods—structural analysis, mathematical modeling, regulatory review, and comparative assessment—enabled a comprehensive study of energy savings potential and the identification of the most effective solutions for industrial enterprises in the Republic of Uzbekistan. Results: the study showed that the greatest energy savings potential lies in pump, fan, and electric drive equipment. The implementation of variable frequency drives reduces energy consumption by 30–40% and pays for itself within two years on average. Additionally, VFDs reduce inrush currents, improve process control, and reduce operating costs. A comprehensive combination of VFDs, reactive compensation, energy-efficient motors, and digital monitoring systems can reduce overall plant energy consumption by 25–45% and increase equipment reliability.